2009
DOI: 10.1097/ta.0b013e3181c0b604
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Examination in Complement With Computed Tomography Scan: An Effective Method for Identification of Cervical Spine Injury

Abstract: In awake and alert blunt trauma patients, clinical examination is a sensitive screening method for c-spine injury. Clinical examination allows for the majority of blunt trauma patients to have their c-spines cleared safely without radiologic screening. Clinical examination in complement with CT scan is a sensitive and an effective method for identification of c-spine injury in awake and alert patients with symptoms of c-spine injury. CT scan is the sensitive and effective test for screening and diagnosis of c-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Regarding the need for CT of the cervical spine, physical examination of the cervical spine is unreliable in patients who are not awake and alert. [17] Although Gonzalez et al [17] question the significance of distracting injuries, reputable organisations such as the Eastern Association for the Surgery of Trauma [18] continue to caution that clinical examination is unreliable in the presence of distracting injuries. The exact definition of distracting injuries remains unclear and calls for clinical judgement.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the need for CT of the cervical spine, physical examination of the cervical spine is unreliable in patients who are not awake and alert. [17] Although Gonzalez et al [17] question the significance of distracting injuries, reputable organisations such as the Eastern Association for the Surgery of Trauma [18] continue to caution that clinical examination is unreliable in the presence of distracting injuries. The exact definition of distracting injuries remains unclear and calls for clinical judgement.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of cervical spine injury among neurologically intact blunt trauma patients with persistent neck pain and negative computed tomography (CT) imaging presents an important clinical challenge. The overall rate of cervical spine injury in blunt trauma patients is 7%-15%, 1 and the NEXUS criteria are widely used to guide clinical evaluation of cervical spine injury. 2 CT scan is the recommended imaging modality, 3 as it is highly sensitive for bony injury.…”
Section: Introductionmentioning
confidence: 99%
“…However, this too is controversial, as MRI has a high false-positive rate, potentially leading to unnecessary cervical collar treatment as well as delay of care while MRI is obtained. 1,2,4,6 To date, studies assessing the efficacy of MRI in blunt trauma patients with negative CT and persistent neck pain have yielded mixed results; [7][8][9][10][11][12][13][14][15] a recent metaanalysis concluded that insufficient data exist for determining whether MRI should be used in this population. 4 Given the paucity of useful data, we performed a retrospective review of neurologically intact blunt trauma patients presenting to our level Copyright 2020 by International Society for the Advancement of Spine Surgery.…”
Section: Introductionmentioning
confidence: 99%
“…4 Current c-spine guidelines, however, require continued spinal immobilization, performance of a clinical examination, referred to as a confrontational examination, and in the presence of cervical spine tenderness, further radiographic studies to assess for possible ligamentous injury. 5 Although c-spine protocols emphasize the importance of a clinical examination prior to c-collar removal, there is little emphasis in the literature to guide physicians on the performance of a proper examination of the cervical spine. Even when steps are appropriately followed, the documentation is often sporadic, communication poor, and the timeliness of collar removal not documented thereby leading to significant legal ramifications where it is often theorized that work not documented is work not done.…”
mentioning
confidence: 99%